2016
DOI: 10.5539/gjhs.v8n10p24
|View full text |Cite
|
Sign up to set email alerts
|

A Path Analysis of Factors Influencing the First Childbearing Decision-Making in Women in Shahrood in 2014

Abstract: Background and Objectives: Normal fertility follows a set of biological, social and cultural rules and regulations; controlled fertility, however, follows the rules and regulations of the family. The present study was therefore conducted to identify the factors influencing the first childbearing decision-making in women living in Shahroud, Iran, in 2014. Materials and Methods:The present descriptive cross-sectional study was conducted on 300 randomly-selected pregnant women admitted to health centers in Shahro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The behavioral intention was defined as a woman's perceived likelihood that she would engage in childbearing. It was evaluated through four 5-point items, including "I will definitely do this (5), I most probably will do this (4), I may do this (3), I possibly will not do this (2), and I will not do this at all (1)" (e.g., "At any time during the next 2 years do you intend to get pregnant?"). The scores of this part ranged from 4 to 20, and its reliability was tested with Cronbach's alpha (0.85).…”
Section: Behavioral Intention Of Childbearing [8 12-14]mentioning
confidence: 99%
See 3 more Smart Citations
“…The behavioral intention was defined as a woman's perceived likelihood that she would engage in childbearing. It was evaluated through four 5-point items, including "I will definitely do this (5), I most probably will do this (4), I may do this (3), I possibly will not do this (2), and I will not do this at all (1)" (e.g., "At any time during the next 2 years do you intend to get pregnant?"). The scores of this part ranged from 4 to 20, and its reliability was tested with Cronbach's alpha (0.85).…”
Section: Behavioral Intention Of Childbearing [8 12-14]mentioning
confidence: 99%
“…The world's total fertility rate has declined from 4.5 births per woman in 1970-1975 to 2.5 in 2005-2010 [1]. A wide range of social, economic, and personal factors, including reproductive behavior, higher levels of education, economic uncertainty (i.e., unemployment or employment opportunities, occupational pressure), partnership shifts (i.e., delay in delaying marriage), and economic goals or challenging housing conditions, lead young people to leave the parental home later, and this has contributed to the decrease in birth rates [1,2]. A review (2014) indicated that parents regarded having completed an educational level, holding a job, and having a stable income and good housing are important factors for their decision-making for childbearing [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fertility decision-making is interactively influenced by four factors (Tough et al, 2007;Ajzen and Klobas, 2013;Kariman et al, 2016): (1) personal attitude toward childbearing which includes personality, emotions, intelligence, value, level of education, and general attitudes; (2) subjective norms, i.e. perceived social pressure to have a child; (3) perceived behavioral control, i.e.…”
Section: Introductionmentioning
confidence: 99%